Tes Minat Karier dalam Konseling Sekolah: Tren Baru - Ahfani, Destri Alviona; Armada, Elsananda Gita; Maulana, Irham Eka (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
Career interest evaluations are crucial in educational guidance initiatives by assisting students in discovering possibilities and recognizing paths that resonate with their character, beliefs, and preferences. Within the framework of contemporary education, interest assessments have advanced from conventional approaches such as the Strong Interest Inventory and the Self-Directed Search. The incorporation of digital technologies, large-scale data analysis, and artificial intelligence has introduced fresh perspectives on how these evaluations are created and presented. These contemporary instruments provide more tailored, engaging, and flexible testing experiences that cater to the varied needs of students. Utilizing technology-driven interest assessments in educational environments can boost the effectiveness of career counseling services, expand access to career-related information, and aid students in making well-informed and realistic choices regarding their future endeavors. This article reviews the latest developments in the utilization of career interest assessments in educational institutions, discusses their advantages and obstacles, and reflects on how they are transforming the function of school counselors in assisting students from academic life into their professional careers.